Indonesia Berpetualang ke Dunia Digital: Society 5.0 - Mikel Ega Wijaya; Aji Wibawa (Universitas Ngeri Malang, 2022)
Society 5.0 offers a platform where technology and innovation can enhance societal well-being by utilizing data and artificial intelligence to solve social issues. In the era of Society 5.0, Indonesia is faced with technology that enables virtual access as if it were physical access. AI based on big data and robots are utilized to support human labor in Society 5.0 technology. In this